Tecnologie riproduttive e tutela della persona Verso un comune diritto europeo per la bioetica - Baldini, Gianni; Soldano, Monica (Studi e saggi, 2007)
Tecnologie riproduttive e tutela della persona. This book emerged from the collaboration between the department of Biolaw of the University of Florence and the non-profit association Madre Provetta. It represents the first stage in a larger editorial project that aspires to contribute study and research to build towards a common European law on bioethics. The authors who have collaborated on this book are among the leading experts, in their respective fields, on questions raised by technologies of reproduction, which are here elaborated at both medical-scientific level and in their relation to sociology, bioethics, law and politics. The various contributions are divided into three specific thematic areas: liberty of reproduction and rights of the individual, pre-implant genetic diagnosis and the freedom and limitations of scientific research.